2005
DOI: 10.1089/jmf.2005.8.488
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Analgesic and Anti-Inflammatory Effects of Nigella sativa Seed Polyphenols

Abstract: Extracts obtained from the seeds of Nigella sativa are used as a spice or remedy for the treatment of various inflammatory diseases. The purpose of this study was to examine the analgesic and anti-inflammatory effects of its polyphenols. N. sativa seed polyphenols were prepared, and analgesic and anti-inflammatory effects were studied in mice and rats using the acetic acid-induced writhing, formalin, light tail flick, carrageenan-induced paw edema, and croton oil-induced ear edema tests. In the acetic acid-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 20 publications
12
71
0
Order By: Relevance
“…Formalin test is believed to be a more valid analgesic model which is better correlated with clinical pain (Tjolsen et al 1992, Ghannadi et al 2005. In this study, the extract caused a dose-dependent decrease in licking time and licking frequency by the rats injected with formalin signifying the analgesic effect of the extract.…”
Section: Discussionmentioning
confidence: 71%
“…Formalin test is believed to be a more valid analgesic model which is better correlated with clinical pain (Tjolsen et al 1992, Ghannadi et al 2005. In this study, the extract caused a dose-dependent decrease in licking time and licking frequency by the rats injected with formalin signifying the analgesic effect of the extract.…”
Section: Discussionmentioning
confidence: 71%
“…Some studies have been conducted to evaluate the anti-inflammatory activity of N. sativa and results are encouraging. [6,7,[13][14][15] However, few studies have been conducted in subacute and chronic model of inflammation. Hence, this study was conducted to evaluate its anti-inflammatory activity in an acute, subacute and chronic model of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Some studies conducted earlier have reported that it do possess significant analgesic and anti-inflammatory activity. [6,7] Even though substantial work has been carried out to ascertain its anti-nociceptive effects, very little has been done to explore its anti-inflammatory effect on subacute and chronic models of inflammation. Hence, we considered it is worthwhile to know whether it has anti-inflammatory activity in a various model of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The potential effect of test compounds observed on the first and second phase of formalin-induced paw licking test have suggested that this effect may be because of its central action (Ghannadi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%